1981
DOI: 10.1029/ja086ia04p02111
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of energetic electrons in the Earth's outer radiation belt during 1968 as observed by the Lawrence Livermore National Laboratory's Spectrometer on Ogo 5

Abstract: An account is given of measurements of electrons made by the LLNL magnetic electron spectrometer (60–3000 keV in seven differential energy channels) on the Ogo 5 satellite in the earth's outer‐belt regions during 1968 and early 1969. The data were analyzed to identify those features dominated by pitch angle and radial diffusion; in doing so all aspects of phase space covered by the data were studied, including pitch angle distributions and spectral features, as well as decay rates. The pitch angle distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 49 publications
3
44
1
Order By: Relevance
“…The lifetimes show a certain dispersion depending on the after storm conditions. For instance, from a diffusion analysis, West et al (1981) found evidence to support the assumption that the most rapid decays are those observed when radial diffusion is weak and pitch angle diffusion is identified as the predominant process responsible for the decay.…”
Section: Data Analysis: Determination Of the Decay Timescalesmentioning
confidence: 88%
See 1 more Smart Citation
“…The lifetimes show a certain dispersion depending on the after storm conditions. For instance, from a diffusion analysis, West et al (1981) found evidence to support the assumption that the most rapid decays are those observed when radial diffusion is weak and pitch angle diffusion is identified as the predominant process responsible for the decay.…”
Section: Data Analysis: Determination Of the Decay Timescalesmentioning
confidence: 88%
“…the electron lifetime) will be given here. In fact, measurements of the lifetimes of energetic electrons are often considered to be the key to the understanding of the transport of these particles; for instance, they constitute key parameters in the determination of pitch angle diffusion rates (West et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…This work was done in the same way as for electrons (e.g., Newkirk and Walt, 1968;Lanzerotti et al, 1970;Tomassian et al, 1972;West et al, 1981;Chiu et al, 1990;Brautigam and Albert, 2000;Brautigam et al, 2005;Ma et al, 2016), protons and other ions/nuclei (e.g., Spjeldvik, 1977;Fritz and Spjeldvik, 1981;Jentsch, 1981;Westphalen and Spjeldvik, 1982;Panasyuk, 2004;Alinejad and Armstrong, 2006;Selesnick et al, 2016). The values of D LL obtained by this method differ from each other by 2 and more orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using HIST electron data, of the quiet-time outer zone and of specific events Blake, 1997, 1998], used similar data analysis methods. Earlier studies of this type [West et al, 1981] used static magnetic field models.…”
Section: Introductionmentioning
confidence: 99%